Experimental observations of self-consolidated hybrid fiber reinforced concrete (SC-HyFRC) on corrosion damage reduction. (15th February 2016) - Jen, Gabriel; Ostertag, Claudia P.
Highlights: Reduced corrosion rates in high performance hybrid fiber reinforced composites. Corrosion associated longitudinal cracks are suppressed in these composites. Control specimens are severely damaged after 2 year exposure to corrosion. Abstract: Correlations between the rate of corrosion damage in reinforced concrete and observable cracking have been established by a multitude of design codes. Based on this relationship, it is inferred that cracking prevention may provide a suitable corrosion protection scheme capable of enhancing the durability/life expectancy of reinforced concrete exposed to potentially corrosive environmental conditions. A self-consolidated hybrid fiber reinforced concrete mixture is tested under a chloride-induced corrosive environment to determine the role of crack suppression in both the initiation and the propagation phases of corrosion damage. It is observed that in the presence of the hybrid fiber reinforcement, chloride migration rates are not significantly altered by the introduction of moderate cyclical mechanical loading in contrast to conventional concrete samples. Furthermore, the accumulation of damage in the propagation phase of reinforcement corrosion is significantly altered by the suppression of splitting cracks emanating radially outward from the reinforcing bar surface. While not a corrosion elimination scheme, the incorporation of hybrid fiber reinforcement is nonetheless capable of prolonging the life expectancy of a given reinforced concrete element and providing an increased measure of durability.